Implementation of Fire Preparedness Activities for Children Aged 5–6 Years at TK Tunas Permata - Komariyah, Kanada; Oktalia, Shela (CV. Creative Tugu Pena, 2025)
Fire Preparedness is a form of disaster response (fire) that emphasizes increasing awareness and resilience toward disasters. This understanding must be instilled in the surrounding community, especially in early childhood, who still do not fully understand what to do when an unexpected disaster occurs. This issue shows the importance of disaster knowledge and risk reduction from an early age to provide understanding and guidance on the steps that should be taken when a threat arises in their environment, thereby minimizing disaster risks. This study aims to determine the implementation of fire preparedness activities for children aged 5–6 years at TK Tunas Permata, Bandar Lampung. The research began with problems identified during preliminary observation, where the researcher found that some children were afraid during the fire preparedness activity, and the teacher's explanation about the activity was not yet concrete enough. As a result, not all children could clearly understand the delivered learning. This study used a qualitative research method with a descriptive qualitative approach. The subjects of the research were teachers at TK Tunas Permata. Data were collected through interviews, observations, and documentation. The data were analyzed qualitatively through data reduction, display, and conclusion drawing. Based on the findings, teachers had made efforts to provide explanations and understanding regarding fire preparedness activities or disaster education. The students at TK Tunas Permata were considered to have developed as expected, particularly regarding social-emotional and language development. Therefore, these activities helped children to cooperate, support one another, and recognize symbols, tools, and fire emergency alarms.